Combined method redesign for the packing area in a peruvian bakery sme provider of national food programs - Quintanilla-Anicama, Mario (2021)
In the bakery industry, it is sought to have zero defective products. It is in the packing; where it is evident, as the last area of the production chain, all the defects generated. Therefore, a combined redesign method is proposed, which consists in the use of Economy of Movement, Ergonomics, Poka Yoke and Method Engineering to reduce defective products in SMEs in the bakery industry. The losses of these generate a reduction of 29.50% for crushed bread and 19.67% of bread on the floor, reducing with the use of this method to 16.20% and 8.38% respectively.